'You feel like your whole world is caving in': A qualitative study of primary care patients' conceptualisations of emotional distress. (May 2017) - Geraghty, Adam WA; Santer, Miriam; Williams, Samantha; Mc Sharry, Jennifer; Little, Paul; Muñoz, Ricardo F; Kendrick, Tony; Moore, Michael
General practitioners are tasked with determining the nature of patients' emotional distress and providing appropriate care. For patients whose symptoms appear to fall near the 'boundaries' of psychiatric disorder, this can be difficult with important implications for treatment. There is a lack of qualitative research among patients with symptoms severe enough to warrant consultation, but where general practitioners have refrained from diagnosis. We aimed to explore how patients in this potentially large group conceptualise their symptoms and consequently investigate lay understandings of complex distinctions between emotional distress and psychiatric disorder. Interviews were conducted with 20 primary care patients whom general practitioners had identified as experiencing emotional distress, but had not diagnosed with major depressive disorder. Participants described severe emotional experiences with substantial impact on their lives. The term 'depression' was used in many different ways; however, despite severity, they often considered their emotional experience to be different to their perceived notions of 'actual' depression or mental illness. Where anxiety was mentioned, use appeared to refer to an underlying generalised state. Participants drew on complex, sometimes fluid and often theoretically coherent conceptualisations of their emotional distress, as related to, but distinct from, mental disorder. These conceptualisations differ from those frequently drawn on in research and treatment guidelines, compounding the difficulty for general practitioners. Developing models of psychological symptoms that draw on patient experience and integrate psychological/psychiatric theory may help patients understand the nature of their experience and, critically, provide the basis for a broader range of primary care interventions.